Pendidikan Ideal dalam Muqaddimah Ibn Khaldun Untuk Memberantas Pengangguran Melalui Minat dan Bakat - Hafidzi, Anwar (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Abstract This thesis explores the idea that the students are able to understand even though they are not educated or accomplished. Some scholars assume, however, that the educational path must go through classrooms. At least this result will give anyone the potential to enhance strong listening skills. The book Diwan Al-Mubtada Wa Al-Khabar Fi Tarikh Al-'Arab Wa Al-Barbar Wa Man 'Asarahum Min Dzawi Al-Sha'ni Al-Akbar by' Abdurrahman Ibn Khaldun with hermeneutic methodology is study using library study with the key source. The outcomes of this research are the principle of fatqu al-lisan by giving preference to basic education abilities by learning soft skills and hard skills of special interest. Ultimately, this power would add to self-confidence in doing business individually and minimize unemployment. Keywords: education, interest, talent, alleviation, unemployment